2021
DOI: 10.1038/s41419-021-03411-6
|View full text |Cite
|
Sign up to set email alerts
|

HOXB4 inhibits the proliferation and tumorigenesis of cervical cancer cells by downregulating the activity of Wnt/β-catenin signaling pathway

Abstract: Homeobox B4 (HOXB4), which belongs to the homeobox (HOX) family, possesses transcription factor activity and has a crucial role in stem cell self-renewal and tumorigenesis. However, its biological function and exact mechanism in cervical cancer remain unknown. Here, we found that HOXB4 was markedly downregulated in cervical cancer. We demonstrated that HOXB4 obviously suppressed cervical cancer cell proliferation and tumorigenic potential in nude mice. Additionally, HOXB4-induced cell cycle arrest at the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…However, previous research showed that HOXB4 directly acts on the Wnt/β-catenin pathway and exerts its anti-tumor effects by reducing Wnt/β-catenin activity. 60 …”
Section: Discussionmentioning
confidence: 99%
“…However, previous research showed that HOXB4 directly acts on the Wnt/β-catenin pathway and exerts its anti-tumor effects by reducing Wnt/β-catenin activity. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, considering the use of HOX protein as cancer therapeutic targets, its interaction with cofactors needs to be determined. Therapeutic values of HOX factors in human cancer are seen in Table 2 ( 4 , 7 , 13 , 14 , 17 , 18 , 22 , 23 , 25 27 , 29 , 31 , 32 , 35 , 41 , 45 , 56 , 57 , 68 , 71 , 72 , 81 , 82 , 84 , 87 , 88 , 90 , 97 , 116 , 117 , 127 , 128 , 132 135 , 137 , 141 , 147 , 148 , 153 , 166 , 167 ).…”
Section: Hox Transcription Factors As Therapeutic Targetsmentioning
confidence: 99%
“…Regulation of HOX factors in various tumor types described in this figure legend. [brain cancer mainly includes the glioma and neuroblastoma (4-11), lung cancer(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), hepatocellular carcinoma(25)(26)(27)(28)(29)(30)(31), bladder cancer(32,33), cholangiocarcinoma(34), head and neck squamous cell carcinoma(35,36), breast cancer(21-23, 37- 54), gastric carcinoma and esophagus cancer(55)(56)(57)(58)(59)(60)(61)(62)(63)(64), prostate cancer and renal carcinoma(43,(65)(66)(67)(68)(69)(70)(71)(72), ovarian cancer (73-79), endometrial cancer and cervical cancer(80)(81)(82)(83)(84), leukemia<...>…”
mentioning
confidence: 99%
“…In a recent study, it was shown to inhibit cancer cell proliferation and further tumorigenesis by inhibiting β-catenin at the transcriptional level by binding to its promoter in cervical cancer cells. Interestingly, several other Wnt related genes were found to be downregulated in cells overexpressing HOXB4, including MYC , whereas genes such as FZD8 , DKK1 , and AXIN2 were upregulated ( Lei et al, 2021 ).…”
Section: Convergence Of Wnt Pathway With Other Signaling Network In Cancermentioning
confidence: 99%